Implementation Of Green Business Ecoprint Industry In Purworejo Regency - Tri Wahyu Lestari; Adi Sucipto; Hesti Respatiningsih (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The ecoprint industry in Purworejo Regency is one of the industries committed to doing business in an environmentally friendly manner. Green business is the main focus in the operation of the ecoprint industry. In this context, green business refers to business practices that aim to improve sustainability and reduce negative environmental impacts. This descriptive qualitative research aims to explain how green business is applied in the ecoprint industry in Purworejo Regency. To find out how green business is implemented in the ecoprint industry in Purworejo Regency, the author interviewed the owner and the production department. Miles and Huberman techniques were used to analyse the data. The results of this study are that the application of green business in the ecoprint industry is reflected in the use of natural materials from plants and natural fibres that have been proven to reduce water and air pollution produced, there are efforts to educate consumers about the importance of environmentally friendly products and their benefits to the environment, and have used environmentally friendly packaging. In addition, the ecoprint industry in Purworejo Regency is implementing an efficient energy management system. Green business in the ecoprint industry is the right step to reduce negative impact on the environment. Overall, the ecoprint industry in Purworejo Regency has successfully operated a business with green business principles. In an era that is increasingly aware of the importance of sustainability, these steps not only provide benefits to the environment, but also enhance the good image of SMEs.